Legal Transformation of Indonesian Sharia Banks Towards Digital Banking in the Era of Industrial Revolution 4.0 - Barkah, Qodariah; SA, Romli; Is, Muhamad Sadi; Andriyani, Andriyani; Bt Ismail, A’dawiyah (al-'adalah, 2024)
Although Islamic banking has been operating in Indonesia since 1992, the institution has not been able to compete with conventional banking. The Government, therefore, intervened by merging several Islamic banks into a single entity, namely Bank Syariah Indonesia (BSI). This merger policy needs to be strengthened further by revising the Islamic Banking Law while encouraging the institution to prepare various steps to respond to the digital banking era. This study examines what kind of legal transformation patterns the Government needs to carry out in preparing Islamic banking institutions to face digital banking in the era of the Industrial Revolution 4.0. This study is juridical-normative research with a philosophical and sociological legal approach. The study results indicate that legal transformation in Indonesian Islamic banking is important to be carried out immediately so that this institution can improve the quality of service to customers along with the shift in banking industry management from a manual system to a full-digital system. For this reason, the Law of the Republic of Indonesia Number 21 of 2008 concerning Islamic Banking needs to be revised again by adding a special chapter that regulates the use of technology in the development of products, services, and operations. In addition, it is also important for the Government to create the Indonesian Sharia Bank Dispute Resolution Institution (LPSBSI), which will function as a unique institution to resolve disputes that occur in Sharia banking.